Girl Athletes in Ethiopia Finding Voice Empowerment Through Sport. Issue 2 (1st June 2022) - Ralls, Kathleen
Abstract: Since sport extends well beyond the routine of practice and competition and leads to the development of skills that affect other areas of life, my study explored whether girl athletes experience greater voice empowerment as a result of playing sport. The term voice empowerment is unique to traditional leadership and character programming; it emerged from recent scholarship in the fields of education, sport, and psychology. In this study, 30 Ethiopian girl athletes aged 13 to 18 completed a 24-item questionnaire that focused on the constructs of sport, voice, and gender equity. My findings suggest that sport along with emotional and academic support, coupled with an effective life skills program, does affect voice empowerment.